Marine-derived polysaccharides: the potential agents against neurodegenerative diseases - Zhu, Lin; Ren, Yuqian; Zhang, Shenghan; Guo, Yunliang; Zong, Jinbao; Liu, Yingjuan (Frontiers in Pharmacology, 2024)
Neurodegenerative diseases are primarily characterized by the selective loss of neurons in the brain, leading to a significant and widespread global public health burden. Although numerous mechanisms underlying neurodegenerative diseases have been elucidated, effective therapeutic strategies are still being explored. Several drugs have been proposed to halt disease progression; however, they often come with severe side effects. Recently, polysaccharides have garnered considerable attention due to their antioxidant, anti-neuroinflammatory, anticholinesterase, and anti-amyloidogenic properties. The ocean contains a large number of animals, plants, algae and fungal species. Its rich sources and wide availability make the research on marine drugs become a hot topic. Recently, polysaccharides dominated by fucoidan and chitosan have been reported to inhibit the progression of neurodegenerative diseases in a variety of ways. In this review article, we provide a comprehensive summary of reported polysaccharides that intervene in neurodegenerative diseases with the aim of exploring their potential as therapeutic agents.